Making an American workforce : the Rockefellers and the legacy of Ludlow - Montoya, Fawn-Amber (University Press of Colorado, 2014)
"Taking an interdisciplinary approach to the policies of the early years of the Colorado Fuel and Iron Company, Making an American Workforce explores John D. Rockefeller Jr.'s welfare capitalist programs and their effects on the company's diverse workforce. Focusing on the workers themselves--men, women, and children representative of a variety of immigrant and ethnic groups--contributors trace the emergence of the Employee Representation Plan, the work of the company's Sociology Department, and CF & I's interactions with the YMCA in the early twentieth century. They examine CF & I's early commitment to Americanize its immigrant employees and shape worker behavior, the development of policies that constructed the workforce it envisioned while simultaneously laying the groundwork for the strike that eventually led to the Ludlow Massacre, and the impact of the massacre on the employees, the company, and beyond. Making an American Workforce provides greater insight into the repercussions of the Industrial Representation Plan and the Ludlow Massacre, revealing the long-term consequences of Colorado Fuel and Iron Company policies on the American worker, the state of Colorado, and the creation of corporate culture. Making an American Workforce will be of interest to Western, labor, and business historians."--